The study of variability of the anterior ethmoidal artery in Hospital Universiti Sains Malaysia - Haw, Lim Eng (2018)
Objective: The aim of this study was to explore the variability of the anterior ethmoidal artery in Malaysian population by using computed tomography. Methodology: This was a cross sectional study of 252 computed tomography of the paranasal sinuses acquired between 1st January 2014 and 31st December 2016. The multiplanar computed tomography images were reconstructed to axial, coronal and sagittal view at 1 mm slice thickness. The relationship of the artery with the skull base, the effect of the pneumatization of ethmoid sinus on this relationship and the distances of the artery from important adjacent reference points were assessed. Results: The anterior ethmoidal foramen was seen in 100% of cases, whereas the anterior ethmoidal canal was only seen in 34.1%. 42.5 % of the anterior ethmoidal artery was found within the skull base, 20.2% at the skull base and the remaining 37.3% coursed freely below the skull base. The prevalence of the supraorbital ethmoid cell and the suprabullar cell were 29.8% and 48.0%, respectively. There was statistically significant association between the presence of the supraorbital ethmoid cell and the position of the anterior ethmoidal artery at the skull base (p < 0.001). The mean height of the lateral lamella of the cribriform plate was 3.74  1.01 mm. The lateral lamella was 1-3 mm in 42.1% and 4-7 mm in 57.9%. With increase in the height of the lateral lamella, the probability for the anterior ethmoidal artery to course freely within the ethmoid sinus increases (p = 0.016). The mean distance of the anterior ethmoidal artery from the skull base was 1.93  2.03 mm, from the orbital floor 21.91  2.47 mm and 49.01  3.53 mm from the nasal floor. Conclusion: This study provides a better understanding of the variability of the anterior ethmoidal artery and its relationship with the skull base. We believe that these details are of paramount importance as a guide for surgeons to ensure a safe endoscopic sinus surgery.